Myasthenia gravis and pregnancy. - Colaço, A (1993)
Four cases of pregnancy in patients with Myasthenia Gravis are presented. No significant pregnancy complications occurred; labour/delivery and puerperium did not present many differences from those expected in healthy women. The review of the literature along with our short experience allows us to conclude that pregnancy in myasthenic patients is a high risk situation, but must be seen with optimism.